Association of distinct fine specificities of anti-citrullinated peptide antibodies with elevated immune responses to Prevotella intermedia in a subgroup of patients with rheumatoid arthritis and periodontitis - Schwenzer, A; Quirke, A; Marzeda, A; Wong, A; Montgomery, A; Sayles, H; Eick, S; Gawron, K; Chomyszyn-Gajewska, M; Łazarz-Bartyzel, K; Davis, S; Potempa, J; et al. (Wiley, 2017)
Objective In addition to the long-established link with smoking, periodontitis (PD) is also a risk factor for rheumatoid arthritis (RA). To elucidate the mechanism by which PD could induce antibodies to citrullinated peptides (ACPA), we examine the antibody response to a novel citrullinated peptide from cytokeratin type I 13 identified in gingival crevicular fluid (GCF), and compare the response to 4 other citrullinated peptides in patients with RA, well-characterized for PD and smoking. Methods The citrullinomes of GCF and periodontal tissue from people with PD were mapped by mass spectrometry. Antibodies to citrullinated peptides from cytokeratin type I 13 (cCK13), tenascin-C (cTNC5), vimentin (cVIM), enolase (CEP-1) and fibrinogen β (cFIBβ) were examined by ELISA in patients with RA (n=287) and osteoarthritis (OA) (n=330), and cross-reactivity assessed by inhibition assays. Results A novel citrullinated peptide cCK13-1 (444TSNASGR-cit-TSDV-cit-RP458) identified in GCF, exhibited elevated antibody responses in RA patients (24%). Anti-cCK13-1 antibodies correlated with anti-cTNC5 antibodies, and absorption experiments confirmed this was not due to cross-reactivity. Only anti-cCK13-1 and anti-cTNC5 were associated with antibodies to the periodontal pathogen Prevotella intermedia (p=0.05 and p =0.001 respectively), but not with antibodies to Porphyromonas gingivalis arginine gingipains. Antibodies to CEP-1, cFIBβ and cVIM correlated with each other, and with smoking and shared epitope risk factors in RA. Conclusion This study identifies two groups of ACPA fine specificities associated with different RA risk factors; one predominantly linked to smoking and shared epitope, the other linking anti- cTNC5 and cCK13-1 to infection with the periodontal pathogen P. intermedia.